MECHANICAL IN THE NOVEL ONE FLEW OVER THE CUCKOO'S NEST. (Heritage, 2022)
The paper compares people and the living world with the mechanical and inanimate world in Ken Kesey's novel One Flew over the Cuckoo's Nest. The use of mechanical terminology, comparison of mеn to robots, and human behavior and human relations to the work of a machine in an industrial environment is not unusual for the twentieth-century literature, especially science fiction, given the development of technology and science: connection of distant parts on the planet, conquering of the space, and splitting of the atom. The man has made a remarkable progress in the field of science, but has he remained the same in that process, or has he “gazed into the abyss” for too long?The analysis that follows raises the question whether the use of mechanical in the novel One Flew over the Cuckoo's Nest is a metaphor or something more. To talk about metaphorical use, we will refer to the paper Metaphor and Mind Style in Ken Kesey's One Flew Over the Cuckoo's Nest by authors Elena Semino and Kate Swindlehurst. On the other hand, we will refer to the ideas of Erich Fromm from a number of his books to show that the mentioned comparison is not only a stylistic figure, but the refection of the process of changing of human nature
Keywords: mechanical, metaphor, mind style, necrophilia, power, Kesey, Fromm.